The Effect Of Capital Structure And Liquidity On Company Value With Profitability As A Moderating Variable - Regina Amalia; Anwar Ramli; Annisa Paramaswary Aslam (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study examines the effect of capital structure and liquidity on firm value, with profitability (ROA) as a moderating variable, using manufacturing companies listed on the Indonesia Stock Exchange during 2020–2024. The research employs a quantitative panel-data design with fixed-effects regression applied to 85 companies (425 firm-year observations). Key independent variables are debt-to-equity ratio (DER) and current ratio (CR), with price-to-book value (PBV) used as a proxy for firm value and ROA as both an explanatory and moderating factor. Model diagnostics including Chow, Hausman, and Lagrange Multiplier tests guided model selection, and robustness checks were conducted to validate results. Findings indicate that profitability (ROA) has a positive and statistically significant effect on firm value, while capital structure (DER) and liquidity (CR) do not exhibit significant direct effects within the tested model. The overall model explains a substantial portion of variation in firm value (adjusted R² ≈ 0.955), and joint significance tests confirm the collective relevance of the predictors. Implications suggest that, in the post-pandemic recovery period, market valuation for Indonesian manufacturing firms is driven more strongly by earnings performance than by leverage or short-term liquidity positions. For practitioners, prioritizing operational efficiency and profit enhancement may yield greater value creation than opportunistic adjustments to leverage or cash buffers. The study recommends further research incorporating external macroeconomic variables and alternative value measures to broaden inference. Future studies should also explore industry heterogeneity, temporal shocks, and nonlinear interactions between financial policy variables and firm performance to strengthen external validity and policy relevance systematically.